PERAN GURU DALAM MENINGKATKAN KEMANDIRIAN ANAK PADA PENGELOLAAN SAMPAH DI SD QUR’ANPRENEUR INDONESIA - Dwi Hadiwijaya; Naomi Diah Budi Setyaningrum; Puspita Sari Jaya, Melinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of teachers in improving students' independence in waste management at SD Qur'anpreneur Indonesia. The study is motivated by the importance of fostering independent character and environmental awareness among elementary school students through waste management activities that actively engage students in the learning process. This study employs David Kolb's Experiential Learning Theory as the theoretical framework to understand how direct learning experiences shape students' attitudes and behaviors. A qualitative approach with a descriptive research method was employed. Data were collected through observations, interviews with teachers and school administrators, and documentation of the implementation of the school's waste management program. The collected data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that teachers play essential roles as educators, facilitators, motivators, mentors, and role models in fostering students' independence through various activities, including waste sorting, classroom cleaning duties, recycling programs, and the development of habits that promote environmental cleanliness. Students' active participation in these activities enhances their sense of responsibility, discipline, environmental awareness, and ability to manage waste independently. Therefore, the active involvement of teachers, supported by school-based environmental programs, makes a significant contribution to developing students who are independent, responsible, and committed to environmental sustainability.